142 PLASMA CELL LEUKEMIA. (10th December 2015) - Walker, B.; Elkins, S.
Abstract : Background: Plasma cell leukemia (PCL) is an aggressive and uncommon plasma cell dyscrasia. It occurs in 2-4% of all cases of multiple myeloma and is diagnosed by a plasma cell count greater than 2 × 109/L in the peripheral blood, and/or plasma cells (PC) comprising greater than 20% of the peripheral leukocytes. Approximately 60-70% of cases present as primary disease and the rest as a secondary transformation of myeloma into a leukemic phase. PCL is characterized by an aggressive presentation, including extramedullary involvement, profound thrombocytopenia, and a high tumor burden marked by elevated lactate dehydrogenase levels. Methods: A 65 year old white male was transferred to our hospital after presenting with low back pain and a gastrointestinal bleed. He was found to have erosive esophagitis as well as renal failure, anemia, thrombocytopenia, and hypercalcemia. After stabilization, the patient was transferred to our hospital. His laboratory workup revealed a calcium of 11.4, creatinine of 4.2, albumin of 2.6, leukocyte count of 17, 300, hemoglobin of 11.4, platelet count of 21, 000, lactate dehydrogenase (LDH) of 694 and β2-microglobulin (B2M) of 16.8. Radiographic studies revealed a compression fracture of the second lumbar vertebra as well as lucencies of his skull. Results: Serum and urine protein electrophoresis and immunofixation revealed monoclonal production of kappa light chains in the urine. Flow cytometry was performed when plasma cells and atypical lymphocytes were found in peripheral blood. A large population of cells marked for CD38, CD56, and CD138 but negative for CD19, CD20, CD45, and CD79A. Cytogenetic analysis revealed monosomy 20 and a deletion of chromosome 1p. The diagnosis of plasma cell leukemia was made and combination chemotherapy was initiated using vincristine, Adriamycin, and dexamethasone. Conclusion: We report a case of primary PCL with an aggressive presentation and a course that is typical of this disease. There was a high tumor burden, as marked by the elevated LDH and B2M. The median survival is approximately seven months. Survival is significantly improved by combination chemotherapy over melphalan and prednisone.